Inclusive e-learning to understand collective memories and identify new uses of African plantations heritage - Eloy, S.; Stellacci, S. (Cultural heritage and social impact: Digital technologies for social inclusion and participation - Symposium Companion, 2021)
Digital globalization has been changing and increasing the flow of information, reshaping perspectives, and actions worldwide, with countless benefits in socio-economic, political, environmental, and cultural realms. However, less-developed countries or historically areas subjected to foreign dependency, such as former colonies, have not benefited from sustainable economic development arising from digital globalization. Moreover, historical biases and underrepresented narratives should be also brought to light, especially in Europe. This ongoing project provides new insights on the Roças, which were built from the mid-19th century in São Tomé and Príncipe (STP) for the production of soft-commodities – mainly cocoa and coffee. This study tackles timely aspects about Roças and its ethical reanalysis by the transnational community. Then, it explores how audio-visual storytelling, serious board game or immersive authentic multisensory tools for visual and auditory stimuli, can be used for making accessible and preserving the value of African plantations heritage. Overcoming the difficulties to reach far and different communities, this project attempts to raise awareness on the tangible and intangible value worldwide. It proposes to pave the way for a dialogue among STP’s community (both local and now living in Portugal) with researchers, policy-oriented organizations, policymakers, local entrepreneurs, and archival curatorial staff. In fact, these groups are often disconnected from consuming and discussing the legacies of colonialism in their twofold aspects, as architectures of violence and as part of the most promising production system. This study offers the opportunity to use inclusive e-learning tools for promoting reflexivity and resilience of STP and European communities when addressing dichotomous values of built heritage. In line with recent research paths on digital cultural heritage conducted by ISTAR team, it is shown how mixed and augmented reality tools enable to convey both inclusive e-learning for a broad community and promote sustainable development.